G’ISHT ISHLAB CHIQARISH TEXNOLOGIK CHIZIG‘I - Odilov Furqat Umarbekovich, Askarov Xasanjon Abduqaxorovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, it is written about the types of equipment classification, performance functions for the production line of ceramic bricks.